Semiotika Sastra: Konsep Puisi-puisi Cinta di Media Sosial Instagram - Riyanto, Bambang; Fitria, Hadaya; Marsella, Emma (TALENTA, 2025)
This research aims to describe the meaning of love-themed poems in the instagram. The study employs Charles Sanders Pierce’s semiotic theory and uses a descriptive qualitative method with a literary semiotics approach. The data source inculude posts from the @gilasastra Instagram account and interviews with its owner. The study analyzes poetic texts to identify their semiotic meanings and interpretations. The findings reveal that @gilasastra is a digital literary figure who utilizes Instagram as a platform for poetry dissemination. The love-themed poems in this account primarily represent interpersonal love, emphasizing human relationships.